If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -5) + 8 = 6x + -2(4 + x) Reorder the terms: 4(-5 + x) + 8 = 6x + -2(4 + x) (-5 * 4 + x * 4) + 8 = 6x + -2(4 + x) (-20 + 4x) + 8 = 6x + -2(4 + x) Reorder the terms: -20 + 8 + 4x = 6x + -2(4 + x) Combine like terms: -20 + 8 = -12 -12 + 4x = 6x + -2(4 + x) -12 + 4x = 6x + (4 * -2 + x * -2) -12 + 4x = 6x + (-8 + -2x) Reorder the terms: -12 + 4x = -8 + 6x + -2x Combine like terms: 6x + -2x = 4x -12 + 4x = -8 + 4x Add '-4x' to each side of the equation. -12 + 4x + -4x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + 0 = -8 + 4x + -4x -12 = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 = -8 + 0 -12 = -8 Solving -12 = -8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| y-60=2(x-120) | | 4x^2+15x-60=0 | | */11=*/12=-11 | | -4p=-24 | | logx=.56 | | f(x)=-3x^2-2 | | 2x^4-66x^2=-64 | | 8x^4-52x^2+44=0 | | 8/12=x/14 | | 7k+9-5k-10= | | 3x-2=6x-1 | | log(2)(6x-3)=2 | | x(x+1)+(x+2)(x+3)=42 | | z=-40x-10y+1850 | | 162=-v+31 | | 182-u=47 | | 3=x/6-5 | | 3x^4-16x^2+16=0 | | cos65=15/x | | 3(x-1)=-18 | | -18y^4/-6y^2 | | 8(3x+4)=18(x+5) | | 12.8=x/4 | | 50/60=10/x | | (2x-1)(4x+4)=0 | | 2/7w=42 | | 7v=14/5 | | 10t+4=-36 | | X(4/9x)=576 | | 8/2=13-3 | | 3log(x^2)+2log(4x)=3 | | log[2](3x-4)=5 |